Fostering social sustainability management through safety controls and accounting: A stakeholder approach in the mining sector - Gunarathne, N.; Samudrage, D.; Wijesinghe, D.N.; Lee, K.H. (Accounting Research Journal, 2016)
Attached

P u rp o se - T h i s p a p e r a im s to id e n t if y th e u s e f u ln e s s o f s a f e t y c o n t r o ls a n d a c c o u n t in g in c o r p o r a t e s o c ia l s u s t a in a b ilit y m a n a g e m e n t in r e s p o n s e to v a r io u s s t a k e h o ld e r s ’ d e m a n d s a n d e x p e c t a t i o n s in th e m in in g s e c to r . D e sig n /m e th o d o lo g y /a p p ro a c h - T h e c a s e s t u d y a p p r o a c h i s f o llo w e d in t h is s t u d y a s it p r o v id e s in -d e p th u n d e r s t a n d in g o f c o m p le x s o c ia l p h e n o m e n a . D a ta c o lle c t io n i s m a in ly b a s e d o n s e m i-s tr u c tu r e d in t e r v ie w s , o n - s it e a s s e s s m e n t s a n d d o c u m e n t a t io n r e v ie w s . V i s i t s w e r e r e p e a t e d a n d c r o s s -c h e c k e d t o e n s u r e th e v a l id it y o f d a ta c o lle c t io n a n d a n a ly s is . F in d in g s - T h e s t u d y id e n t if ie s a r e c ip r o c a l r e la t io n s h ip b e t w e e n s t a k e h o ld e r m a n a g e m e n t s t r a t e g ie s a n d th e s a f e t y c o n tr o l s y s t e m th a t e n c a p s u la t e s a m ix o f le a d in g a n d l a g g in g k e y s a f e t y p e r fo r m a n c e in d ic a to r s (K S P ls ). A s a f e t y c< m tro l s y s t e m w it h th e r ig h t m ix o f K S P I s d r iv e s c o r p o r a t e v a lu e -c r e a tio n b y in s t ig a t in g in te r n a l o r g a n iz a t io n a l c h a n g e s . Y e t, th e s t a k e h o ld e r s ’ e x p e c t a t io n s a n d p r e s s u r e s a r e d e p e n d e n t o n n a tio n a l, h is to r ic a l, c u ltu r a l a n d s o c ia l s e t t i n g s a n d in s t it u t io n s t h a t w ill im p a c t o n th e s a f e t y c o n t r o ls a n d s a f e t y a c c o u n t in g in a s u b s t a n t ia l w a y . O rig in a lity /v a lu e - T h e p a p e r d e m o n s t r a t e s th e u s e f u ln e s s o f s a f e t y c o n t r o ls a n d a c c o u n t in g in c o r p o r a te s t a k e h o ld e r m a n a g e m e n t in th e m in in g s e c to r in S r i L a n k a . T h e p a p e r , b y a d d r e s s in g h o w s a f e t y c o n tr o l s y s t e m s a n d a c c o u n t in g m e e t v a r io u s s t a k e h o ld e r d e m a n d s a n d e x p e c t a t io n s , p r o v id e s n e w in s ig h t s in to c o r p o r a te s o c ia l s u s t a in a b ilit y p e r fo r m a n c e in m in in g c o m p a n ie s a n d th e r o le a n d im p lic a t io n s o f s u s t a in a b ilit y (m a n a g e m e n t ) a c c o u n t in g .
Keywords: Mining industry; Stakeholder management; Health and safety; Corporate social sustainability; Leading and lagging indicators; Safety accounting